Green Tea Polyphenols Alleviate Hydrogen Peroxide-Induced Oxidative Stress, Inflammation, and Apoptosis in Bovine Mammary Epithelial Cells by Activating ERK1/2–NFE2L2–HMOX1 Pathways - Ma, Yanfen; Ma, Xuehu; An, Yanhao; Sun, Yishuo; Dou, Wenli; Li, Muyang; Bao, Hua; Zhang, Chunhua (Frontiers in Veterinary Science, 2022)
Oxidative stress (OS) is one of the main limiting factors affecting the length of lactation and milk quality in dairy cows. For high-producing dairy cows, the OS of mammary glands is a serious problem. Green tea polyphenols (GTP), found mainly in tea, are a combination of many phenols. GTP have a good effect on anti-oxidation, resisting inflammation, obesity, improving fat cell metabolism and lowering blood lipid. Therefore, we studied the role of GTP on oxidative stress in dairy cows, and further investigated whether GTP alleviates oxidative damage of bovine mammary epithelial cells (BMECs) induced by hydrogen peroxide (H2O2) and its underlying molecular mechanism. In this study, 500 µM of H2O2 for 12 h incubation was chosen as the condition of the oxidative stress model of BMECs. In addition, the present results found that treatment with GTP alleviated the oxidative damage induced by H2O2 [The activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT) were significantly increased and the contents of malondialdehyde (MDA), 8-isoprostaglandin (8-iso-PG), 8-oxo-deoxyguanosine (8-OHdG) and protein carbonyl (PC) and caspase-3 and caspase-9 activities were significantly reduced]. These effects are related to the activation of the erythrocyte-derived nuclear factor 2-like protein 2 (NFE2L2) signaling pathway and the inactivation of the caspase/bcl-2 apoptotic pathway. When NFE2L2 short interfering RNA (siRNA) was used to down-regulate the expression of NFE2L2 in cultured BMECs, NFE2L2-siRNA transfection abolished the protective effect of GTP on H2O2-induced intracellular reactive oxygen species (ROS) accumulation and apoptosis. In addition, the mitogen-activated protein kinase (MAPK) inhibition test further proved that GTP relieved H2O2-induced oxidative damage by activating the NFE2L2 signaling pathway was achieved by activating the extracellular-regulated kinase 1/2 (ERK1/2) signaling pathway. Overall, the results indicate that GTP has a beneficial effect on the redox balance of BMECs. In addition, GTP might be a latent antioxidant in vivo, which can be administered to ruminants during stressful periods such as the perinatal period.